KILL THE STEREOTYPING ON WOMEN DIRECTORSHIP: EMPIRICAL EVIDENCE FROM TOP 10 MALAYSIA COMPANIES WITH GOOD CORPORATE GOVERNANCE - Mohamad Hafiz Rosli; Farhana Hasbolah (International Journal of Accounting, Finance and Business, 2022)
Women's directorship is one of the crucial parts of business leadership. The Malaysian Code of Corporate Governance (MCCG) 2021 states at least 30% of women directors. However, statistics show that women's directorship has been underrepresented on the board of directors. Thus, this study is intended to discover the characteristics of women directorship among Malaysian Top 10 public listed companies with good corporate governance 2020. Secondary data gathered from Company’s Annual Report 2020 and descriptive statistics are used to present the data and discussion. The finding reveals that women director is almost widely accepted as board members. Other characteristics such as type of directorship, education level, education field, industrial experiences, age and culture are also interrelated with the women directors. This finding provides insights to the policymakers, government and public listed companies to formulate the women policies as the board of directors and enhances literature.